Analysis of adaptation potentials of kick boxers’ cardio-vascular system - L.V. Podrigalo; A.A. Volodchenko; O.A. Rovnaya; L.A. Ruban; K.M. Sokol (Pedagogics, Psychology, Medical-Biological Problems of Physical Training and Sports, 2017)
Analysis and assessment of athletes’ adaptation potential are important components of effective selection and prediction of sports successfulness. Purpose: study and analysis of kick boxers’ cardio-vascular system’s adaptation potentials under standard physical load and in recreation. Material: in the research kick boxers (n=17, students) participated. The athletes were divided into 2 groups, depending on reaction to physical load: 1st group - athletes with normotonic type of reaction (n=9, age 17.56±0.80 years); 2nd group - athletes with reaction different from normotonic (n=8, age18.25±0.88 years). Indicators of cardio-vascular reaction type and tolerance to physical load were found with the help of PWC170 test. Results: we confirmed similarity of kick boxers’ reaction to physical load. After 1st stage of physical load heart beats rate was noticeably lower in the 1st group. After 2nd stage of load systolic blood pressure was lower in the 1st group. After load, in the 1st group heart beats rate and systolic BP restored quicker. Reduction of heart beats rate under load in 1st group can serve as a proof of better adaptation mechanisms. Conclusions: training of athletes with periodic control of electric cardiogram under physical loads permits to assess functional state of cardio-vascular system; its adaptation and correspondence to definite physical loads. Such approach permits not to admit progressing of cardio-vascular system’s pathological state.